Whole Genome Analysis of Sugarcane Root-Associated Endophyte Pseudomonas aeruginosa B18—A Plant Growth-Promoting Bacterium With Antagonistic Potential Against Sporisorium scitamineum - Singh, Pratiksha; Singh, Rajesh Kumar; Guo, Dao-Jun; Sharma, Anjney; Singh, Ram Nageena; Li, Dong-Ping; Malviya, Mukesh K.; Song, Xiu-Peng; Lakshmanan, Prakash; Yang, Li-Tao; Li, Yang-Rui (Frontiers in Microbiology, 2021)
Sugarcane smut is an important fungal disease causing a major loss in sugar yield and quality. In this study, we isolated an endophytic strain B18 from a sugarcane root, which showed plant growth-promotion, hydrolytic enzyme production, antifungal activity against sugarcane pathogens (Sporisorium scitamineum, Ceratocystis paradoxa, Fusarium verticillioides), and presence of nifH, acdS, and antibiotic genes (hcn, prn, and phCA) under in vitro conditions. BIOLOG(R) phenotypic profiling of B18 established its ability to use various carbon and nitrogen sources and tolerate a range of pH, and osmotic and temperature stresses. Whole-genome analysis of B18, identified as Pseudomonas aeruginosa, showed that it consists of a single circular chromosome of 6,490,014 bp with 66.33% GC content. Genome annotation has identified 5,919 protein-coding genes, and 65 tRNA, and 12 rRNA genes. P. aeruginosa B18 genome encodes genes related to ethylene, nitrogen (nifU, norBCDERQ, gltBDPS, and aatJMPQ) and phosphate (pstABCS and phoBDHRU) metabolism, and produce indole-3-acetic acid and siderophores. Additionally, genes encoding hydrolases, oxidoreductases, and those associated with biocontrol mechanisms (hcnABC, phzA_B, phzDEFGMS, and pchA), colonization (minCDE and lysC), and biofilm formation (efp, hfq, flgBCDEFGHI, and motAB) and those associated with metabolism of secondary metabolites. Collectively, these results suggest a role for P. aeruginosa B18 in plant growth enhancement and biocontrol mechanisms. P. aeruginosa B18 strain was found to be an efficient colonizer in sugarcane and improve the growth through modulation of plant hormone production and enhanced host-plant resistance to smut pathogen S. scitamineum-in a smut susceptible sugarcane variety (Yacheng71-374). These biocontrol and plant growth promotion properties of P. aeruginosa B18 area discussed in this report.